Empowering Skepticism: Neuroethics Engagement with Tibetan Buddhist Monastics - Specker Sullivan, Laura (Frontiers in Communication, 2021)
Neuroethics has been incorporated into neuroscience training through the Science for Monks program since 2016. In this article, I describe this in-progress effort and I consider how the program has changed since this first year to develop into a pilot program in community-engaged participatory research with the monastic community. The current goals of the project are to train the monastics in social science research skills as a means of empowering them to harness their deep knowledge of ethics and to bring it to bear on ethical challenges in neuroscience, neurology, and neurotechnology.